The self-confidence of dental students in oral surgery = La autoconfianza de los estudiantes de odontología en cirugía oral - Sari, Merve
The aim of this study is to evaluate the self-confidence of undergraduate students and thus to highlight the strengths and weaknesses of oral surgery education from the students' perspectives. A survey was conducted by preparing a questionnaire to assess the the self-confidence of students in performing oral surgery. Survey questions have been imported to Google Forms®. It was then electronically delivered to the students through the Turkish Dental Association. Regarding the data, besides the frequency and percentage distributions, the relationship between the variables was analyzed using the Chi-Square test. A total of 615 students, including 386 female and 229 male students, participated in this study. Of the students, 62.4% were 5th year and 37.56% were 4th year students. According to the survey, it was observed that male students and 5th year students were in general more confident in themselves. Students had low self-confidence in differentiating between odontogenic and non-odontogenic pain and recognizing malignant lesions or lesions with high malignant potential. In the oral surgery curriculum, subjects in which the students have issues should be identified and more emphasis should be placed on them. Oral pathology as well as head and neck anatomy courses should be emphasized further, priority should be given to case-based courses, and reminder presentations should be made at certain intervals. In addition, considering that practice is important for gaining self-confidence, students must practice more under the supervision of instructors in the areas in which they feel inadequate.